Cold-formed steel framing walls with infilled lightweight FGD gypsum Part II: Axial compression tests. (November 2018) - Wu, Hanheng; Chao, Sisi; Zhou, Tianhua; Liu, Yunxiao
Abstract: An innovative cold-formed steel (CFS) framing wall with infilled lightweight flue gas desulfurization (FGD) gypsum was presented in Part I by Wu et al. (Submitted for publication) [1], in which cyclic loading tests were performed. This paper focuses on axial compressive behavior of the innovative wall. Eight full-scale specimens of infilled and unfilled CFS walls were tested under axial compressive loads. The failure modes, axial load-deformation responses, axial load-strain responses, axial compressive stiffness and axial bearing capacity of the specimens were investigated. In the tests, gypsum-encased wall studs lost their bearing capacity in the limit state of strength failure instead of buckling failure. Clear evidences were obtained that axial bearing capacity and axial compressive stiffness of the walls were significantly improved by infilling the gypsum. Compared with the unfilled walls, the maximum loads of the infilled were enhanced by 1.88–2.99 times. When the infilled specimens reached to their maximum loads in which the encased studs were in or close to yield state, but at that moment, the infilled gypsum cannot make full use of its axial bearing capacity in total sections. In addition, the finite element models of infilled walls were developed and validated using experimental results. Parametric studies showed that wall thickness, CFS thickness, and compressive strength of infilled gypsum had an impact on axial compression capacity of the walls, but the friction coefficient between CFS and infilled gypsum had little effect on axial bearing capacity. In this scenario, a modified superposition method was proposed to quantify axial bearing capacity of the infilled walls, and the reduction factor γ  = 0.6 was then suggested in the paper, which shows a good agreement with experimental and numerical values. Highlights: Axial loading tests conducted on infilled CFS shear walls. Encased wall studs lose their bearing capacity in the limit state of strength failure instead of buckling. A modified superposition method was proposed to quantify the axial-bearing capacity of the infilled walls.